Experimental test of coupling effect on CLT angle bracket connections - Liu, Jingjing; Lam, Frank (Engineering structures, 2018)
•The coupling effect of shear force and tension force on CLT angle bracket connections was investigated experimentally. Failure modes, key mechanical properties, force–displacement relationship, and energy dissipation were used to evaluate the structural behavior of CLT angle bracket connections under bi-directional loading.•Strong coupling effect of shear and tension behavior was found for CLT angle bracket connections under bi-directional loading. Additional tension load weakened the shear performance of angle bracket connectors, especially the strength, energy dissipation capacity and stability.•More brittle failure modes were found during tests with additional tension load. The hysteresis behavior changed dramatically with the introduction of additional tension force.•The test results show the necessity of considering the coupling effect in future numerical analysis of CLT angle bracket connections. In this paper, the coupling effect of axial and lateral loading on Cross Laminated Timber (CLT) angle bracket connections is investigated through experimental tests. Monotonic and cyclic tests of the connections were carried out in shear, with different levels of constant force applied in tension simultaneously. Specimens subject to four different levels of tension forces were tested and the results were analyzed in terms of key mechanical characteristics of those connections including strength, stiffness, ductility, strength/stiffness degradation, equivalent viscous damping and energy dissipation. The results show that shear and tension for angle brackets are strongly coupled. Co-existent of tension force reduces the lateral strength and stiffness capacity of the connection significantly. Under complex loading, the gap between nail and wood embedment mitigates and the friction increases, resulting in the reduction of pinching effect; hence, the energy dissipation capacity drops under larger deformation. The study gives a better understanding of hysteretic behavior of angle bracket connections for CLT where rocking motions occur, and provides reliable data for future numerical analysis of CLT structures.